Skills for Preventing Injury in Youth: Evaluating Change in Adolescent Alcohol Use, Violence, and Road-Related Injuries. Issue 6 (September 2021) - Buckley, Lisa; Reveruzzi, Bianca; Dingli, Kelly; Chapman, Rebekah L.; Sheehan, Mary
This study evaluated the injury prevention program, Skills for Preventing Injury in Youth (SPIY) for Year 9 students (aged 13–14 years). The aim of SPIY was to reduce adolescent injury by reducing engagement in risk-taking behaviors. A randomized controlled trial was conducted and data analyzed with 32 schools, N = 2, 739 students at baseline. Students' self-reported injury prior to the commencement of SPIY and at 6 and 12 months after the program concluded. For those with few protective factors at baseline, there was less increase in alcohol-related injuries and a decline in violence-related injuries for intervention compared with control students. Findings showed the SPIY program can be effective in reducing adolescent injury for those with few promotive factors.